La (Re)construction Francaise De L'analyse Infinitesimale De Leibniz: 1690-1706: by Sandra Bella, Paris, Classiques Garnier, 2022, 548 pp., $130.00 (hardback), ISBN 9782406123880. - Lugaresi, Maria Giulia (Annals of Science, 2025)
The article focuses on a comprehensive study of the reception of Leibnizian calculus in France from 1690 to 1706, emphasizing the contributions of the 'groupe malebranchiste,' a scientific community led by Nicolas Malebranche. The author, Sandra Bella, divides the analysis into three phases: the preparatory period for infinitesimal methods, the genesis of l'Hospital's influential work on calculus, and the subsequent disputes within the Paris Royal Academy of Sciences regarding the new calculus. Bella highlights the political and intellectual dynamics of this period, including the correspondence among key mathematicians and the eventual acceptance of Leibnizian calculus despite initial resistance. The book serves as a detailed resource for understanding the historical context and evolution of mathematical thought in early modern Europe.